Oxygen Therapy in Children - An Update - Sarkar, Probir Kumar; Rahman, Md Shakibur (Dhaka Shishu (Children) Hospital Journal, 2021)
In 1774, Joseph Priestley of England discovered the colorless, odorless, tasteless gas that Antoine Lavoisier named oxygen.Oxygen is a lifesaving drug has safe dose ranges, adverse physiologic effects, and toxic manifestations that are associated with higher doses and prolonged use. So, the administration of oxygen should be done with as much care and attention as any other drugs. Oxygen is transported in the blood in two ways: dissolved in the serum and in combination with hemoglobin.Children with any of the following signs are likely to have hypoxemia: central cyanosis, nasal flaring, inability to drink or feed due to respiratory distress, grunting with every breath and depressed mental state, severe lower chest wall indrawing, tachypnea or head nodding. The sources of oxygen and its delivery depend on the facility and the availability of resources. Most commonly use devices for oxygen delivery are nasal cannula, nasal prongs, simple face mask. An FiO2 of >0.5 is considered toxic. After only a few hours of breathing 100% O2, mucociliary function is depressed and clearance of mucous is impaired followed by nonproductive cough, substernal pain and nasal stuffiness may develop. More prolonged exposure to high O2 tention may lead to changes in the lung that mimic adult respiratory distress syndrome. In premature neonates, lower SpO2 may be targeted to reduce the toxic effects of oxygen therapy, such as retinopathy of prematurity or bronchopulmonary dysplasia. DS (Child) H J 2018; 34(1) : 48-54